Strength, Weakness, Opportunity and Challenges (SWOC) Analysis of Recruitment Policies for Educators in Punjab - Nadia Bukhari, Sami Ullah Joyia (JELM, 2023)
The purpose of the study was to evaluate the strengths, weaknesses, opportunities and challenges of the recruitment policies for educators in Punjab to identify the impediments that hindered the experts to improve the education system. The research study was descriptive in nature for which a survey was conducted through questionnaires and data collected from different stakeholders. The objectives of the study were: (1) To analyze the existing structure of recruitment system in Punjab Education Department, (2) To analyze the strengths, weaknesses, opportunities and challenges of recruitment process of educators in Punjab. All the District Administrators, Educational Administrators and Educational Managers of Secondary Schools of Punjab Province were population. The sample of the study was consisted of 1/3 of population. Collected data was analyzed by using different statistics includes frequency, percentage and mean score. The existing structure of recruitment policies of educators and strengths, weaknesses, opportunities, and challenges of recruitment process were analyzed. The data reflected that the recruitment policies for educators could not meet the requirement because of unavailability of standardized structure of interview, lake of the trends in multi-disciplinary professions, lake of motivation and inadequate assessment through NTS. The study explored that a comprehensive recruitment policy might be framed to provide clear guideline, to establish separate recruitment cell, to establish an interventional advisory board, to provide a clear strategy for interview and provide clear terms & conditions for applicants.